PRECISION IN EVALUATION OF SIMPLE AND STRATIFIED RANDOM SAMPLING IN THE SCIENTIFIC JOURNALS MARKET - Lojanica, Nemanja (International Journal of Economic Practice and Policy, 2017)
When conducting economic research, very important issue is the choice of an adequate sample. More specifically, the goal is to select a sample that accurately reflects the characteristics of the basic set. In this regard, the present study investigated the precision in the evaluation of the simple and stratified random sampling within the scientific journals market. As a corresponding feature value, the factor of the impact was selected. The results of the conducted analyses, showed that stratified random sample provides more precise evaluation than the simple sample. More specifically, the calculated mean of the stratified sample is closer to the average of the population, and the variance of the average of the stratified sample is smaller. Thus, in using stratified sampling, the less deviation from the population parameters was recorded. Those advantages of informing a stratum should be taken into account when establishing the appropriate samples in the economic analysis.